A case report of a patient presented with skin ulcer after treatment of lenvatinib - Serin Cha; Dong Woo Kim; Jung Wan Choe; Tae Hyung Kim; Seung Young Kim; Jong Jin Hyun; Sung Woo Jung; Ja Seol Koo; Young Kul Jung; Hyung Joon Yim (Korean Liver Cancer Association, 2021)
A 60-year-old man diagnosed with unresectable hepatocellular carcinoma (HCC) presented to the hospital with pain in the perineal region. He had been taking lenvatinib every day for 2 months after he was diagnosed with HCC with metastases to the lymph node, small bowel mesentery, and retroperitoneal space. Enhanced abdominal computed tomography revealed mild elevation in intensity in the perineal subcutaneous tissue with subcutaneous emphysema. The patient was diagnosed with Common Terminology Criteria for Adverse Events grade 3, skin ulceration of stage IV with full-thickness skin loss and tissue necrosis in the muscular layer. The patient was taken off the medication with prescription of antibiotics, and after 3 weeks, the skin has fully recovered. This is the first report of an HCC patient who presented with a skin ulceration of stage IV after lenvatinib treatment. We recommend stopping the medication immediately and changing to alternative treatments with appropriate supportive care.